2004
DOI: 10.1097/00004647-200412000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphodiesterase 3 Inhibitor Cilostazol Dilates Large Cerebral Arteries in Humans Without Affecting Regional Cerebral Blood Flow

Abstract: Summary:Cilostazol, an inhibitor of phosphodiesterase (PDE) type 3, is used clinically in peripheral artery disease. PDE3 inhibitors may be clinically useful in the treatment of delayed cerebral vasospasm after subarachnoid hemorrhage. The authors present the first results on the effect of cilostazol on cerebral hemodynamics in normal participants. In this double-blind, randomized, crossover study, 200 mg cilostazol or placebo was administered orally to 12 healthy participants. Cerebral blood flow was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Although the present study demonstrated that cilostazol induced vasodilation of the resistance-sized blood vessels, cilostazol was reported to have no effect on human regional cerebral blood flow [14]. This discrepancy between the in vivo and in vitro experiments may depend on (1) species differences, (2) differences of circumstances inside or surrounding the arterioles, such as existence of plasma or blood cells, changes of intracranial pressure, changes of diastolic pressure, and changes of intraluminal flow velocity, (3) changes of distribution of resistance in cerebral vasculature induced by autoregulation, and (4) relatively weak effect of cilostazol on arterioles compared with large cerebral arteries.…”
Section: Discussionmentioning
confidence: 81%
“…Although the present study demonstrated that cilostazol induced vasodilation of the resistance-sized blood vessels, cilostazol was reported to have no effect on human regional cerebral blood flow [14]. This discrepancy between the in vivo and in vitro experiments may depend on (1) species differences, (2) differences of circumstances inside or surrounding the arterioles, such as existence of plasma or blood cells, changes of intracranial pressure, changes of diastolic pressure, and changes of intraluminal flow velocity, (3) changes of distribution of resistance in cerebral vasculature induced by autoregulation, and (4) relatively weak effect of cilostazol on arterioles compared with large cerebral arteries.…”
Section: Discussionmentioning
confidence: 81%
“…Cilostazol, a phosphodiesterase 3 inhibitor is a platelet aggregation inhibitor, which also has an effect on smooth muscle cells 183. Cilostazol has been shown to ameliorate vasospasm in experimental models 184.…”
Section: Treatment Of DCImentioning
confidence: 99%
“…The mechanism is mainly explained by cerebrovascular dilatation, which occurs with other vasodilators such as nitrates, dipyridamole, sildenafil, and calcium antagonists. However, there was no withdrawal from treatment in patients receiving cilostazol due to headache 2830. The haemodynamic effects of cilostazol were minimal.…”
Section: Discussionmentioning
confidence: 98%